PENINGKATAN MEMBACA PERMULAAN MELALUI MODEL GAME BASED LEARNING BERBANTUAN MEDIA SUKAPIN DI SEKOLAH DASAR - vebby meilia; erik aditia ismaya; lintang kironoratri (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2026)
Early reading skills among elementary school students remain low, while the implementation of Game-Based Learning using SUKAPIN media with first-grade students has rarely been studied. This study aimed to determine the effectiveness of the Game-Based Learning model using SUKAPIN media on the early reading skills of first-grade students at SD Negeri 1 Ngembal Kulon. The study employed a quantitative approach using an experimental method and a One-Group Pretest-Posttest design. The sample consisted of 28 students selected via the saturated sampling technique. Data were collected through tests, observations, interviews, and documentation, and subsequently analyzed using the N-Gain test and hypothesis testing. The results showed that the students' average score increased from 47.85 in the pretest to 77.85 in the posttest, with an N-Gain score of 0.547 (moderate category). Hypothesis testing yielded a significance value of 0.000 (<0.05), indicating that the Game-Based Learning model using SUKAPIN media is effective in improving students' early reading skills. This study offers a game-based learning alternative that teachers can implement to enhance early reading skills in a more interactive manner. Keywords: Beginning Reading, Game Based Learning, Elementary School, Instructional Media.